ڕۆڵی تەلەڤیزیۆن لە ناساندنی دیپلۆماسی گشتیدا - حسن, پ. ی. د. هێمن مجيد; عبدالله, دێكان کاوه (Sulaimani Journal for Humanities, 2021)
This research deals with public diplomacy which is vital and contemporary subject. This type of diplomacy has its own significance for countries and nations. Particularly, for nations trying to determine their destiny toward independency. The aim of this research is to reveal the way Kurdish TVs work introducing public diplomacy and used methods. For that purpose, the researcher has consulted coverage methods and report tools. In the study, the history of public diplomacy concept, its definitions, factors of breaking out and developments technological communications have been indicated. We, in the research, reached a point that kurdish TVs like other international channels have benefited from development s of technology to introduce public democracy, but the question of allocating special journalism remained unanswered.